PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - TRI WIDYAWATI, NITA; TRI WIDYAWATI, NITA (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract:The main purpose company is to improve the company. Firm value affected financial performance as measured by the profitability. CSRallegedly moderate relation of financial performance of the firm value. In 2010-2012 manufacturing companies indicate level of PDB in highest position, but its trade volume is in lowest position. Research is aimed to know influence on the company financial performance and knowing disclosure of CSR to strengthen influence of financial performance against value of companies. The sample of this research uses a manufacturing company listings on IDX in 2010-2012. Technique of data analysis in this study uses the classic assumption and moderation MRA. The results showed that financial performance does not affect value of the company due to the global crisis of 2008 and government’s policy in 2012. CSR does not strengthen influence of the financial performance of the company’s value since CSR is required to do activities of the company. Keywords:financial performance (ROA), corporate social responsibility (cost allocation), firm value (Tobin’s Q)